ANALISIS SEGMENTASI DAN PETA POSISI PERGURUAN TINGGI SWASTA DI MALANG DAN SURABAYA - Sari Wijayanti (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2018)
Higher education in Indonesia is increasingly regarded as a market. In general, universities have recognized the importance of marketing to provide information on existing products such as majors, courses, certifications, lecturers’ skill, facilities, scholarship, etc. The need of marketing become prominent because the more known a college the more prospective students. Based on data obtained from one of the marketing department of publicuniversity in Malang, admission of new students (2007 - 2016) did not experience a significant increase. Sampling technique used is probability sampling by method stratified sampling (layered sampling techniques). 200 respondents have less allowance than IDR 1.000.000 that is 53.05% respondents have lower to medium economic ability. 67.37% respondents or meaning thatthe market targeteted from people with middle economy capability. Percentage of university selection by respondents based on all variables such as product, price, location, promotion, human resources, physical evidence and process for each university is almost big as 94,57% out of the total value of diversity entirely.  Keywords:  segmenting, targeting, positioning, marketing strategy